Enfoques teóricos para el estudio de la cooperación empresarial - Muñoz Martín, Juan; Montoro Sánchez, María Ángeles (Cuadernos de Estudios Empresariales, 2007)
Alliances are increasing in frequency and strategic importance. Strategic alliances have been examined from different theoretical approaches generating confusion and unclear understanding of this concept. The purpose of this paper is clarify the concept and the rational for strategic alliances from different theoretical perspectives. In this respect, different approaches should be regarded as complementary views rather than substitutive views.